PEMANFAATAN PEMBELAJARAN INFORMATIKA UNTUK MENGEDUKASI PENTINGNYA KEAMANAN DATA PRIBADI SAAT BERINTERNET KEPADA SISWA KELAS 10 SMAN 1 CIRUAS - Nova Amelia Putri; Sarah Caesarani (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Field Experience Practice (PPL) activities are professionalism building activities in the teaching field that can be directly applied in field practice. PPL is intended to train students to apply knowledge and methods during lectures in the field. PPL activities were carried out at SMAN 1 Ciruas, especially for class 10 students at SMAN 1 Ciruas. PPL carries out teaching and learning activities in class, presenting material regarding information and communication technology, as well as testing understanding regarding the material that has been presented. Activities were carried out for 3 weeks. The result of the activity is the enthusiasm of the students in participating in PPL activities because they are carried out interactively. Apart from that, it is hoped that students can apply the material in everyday life and can share and help others to avoid cybercrime